Investigating the Characteristics of Modified Bitumen with Polyphosphoric Acid Polymers and Recycled Rubber - Najfabadi, Sajad Chavoshi; Khabiri, Mohammad Mehdi; Sanij, Hamed Khani (Communications - Scientific Letters of the University of Zilina, 2024)
The impact of polyphosphoric acid (PPA) polymers and crumb rubber (CR) on bitumen's properties to enhance its performance was examined in this study. Laboratory samples were created with varying percentages of PPA (0.5 % to 2 %) and CR (6 % to 18 %) and subjected to extensive testing. Findings indicated that the combination of PPA and CR led to notable improvements in bitumen performance, including increased viscosity, softening point, elasticity, and recovery rates at elevated temperatures. Specifically, samples with 18 % CR and 1.0 % or 2.0 % PPA demonstrated exceptional rheological properties and strength. The optimal combination (18% CR and 1.0% PPA) resulted in a uniform structure, while the maximum CR content did not compromise bitumen integrity. Both additives effectively minimized temperature sensitivity and aging, enhancing the bitumen's performance class significantly.
Keywords: rutting resistance; modified bitumen; performance grades (PG); polyphosphoric acid polymer (PPA) waste rubber (CR) powder